Entrepreneurship Education and the Challenges of Graduate Employability in Nigeria - (:unkn) unknown (My University, 2018)
Abstract—Entrepreneurship education has been identified as a major means of assisting youths and even adult to acquire desired skills and capacities to be self-reliant or self-employed, particularly to prepare them to be able to set up their own ventures and manage them profitably. Hence, there is a great need to look at the challenges in Entrepreneurship education in Nigerian universities and proffer solutions to the identified problems. The study adopted a review methodology approach of extant literatures and publications in the last decade. The study revealed that there are several factors impeding the success of entrepreneurship education in Nigeria, which might be affecting the production of employable graduates in our universities. The study provided a panacea that will helpimprove entrepreneurship education in Nigeria, and create graduates that will not only be job seekers, but will be job makers in Nigeria. Conclusively, the study also, suggested areas for further studies based on the limitation of the study.
Keywords: African Research